Shortcut Evaluation of Chemical Carbon Dioxide Utilization Processes - Müller, Karsten; Arlt, Wolfgang (Chemical Engineering & Technology, 2014)
Chemical utilization of carbon dioxide seems to be an attractive option for the mitigation of greenhouse gas emissions. However, the respective processes themselves cause substantial greenhouse gas emissions. To achieve a good CO2 balance, it is necessary not only to fix carbon but also to do this efficiently in terms of reactant supply and energy demand. An evaluation of the CO2 balance requires detailed process simulation for the utilization reaction and the supply chain. To allow a quick evaluation of the potential to mitigate emissions, a number of estimation methods are presented.
Keywords: Carbon dioxide; Carbon footprint; Chemical utilization; Greenhouse gas mitigation